2018
DOI: 10.1016/j.jad.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and posttraumatic stress disorder in adult civilian survivors of war who stay in war-afflicted regions. A systematic review and meta-analysis of epidemiological studies

Abstract: Our findings suggest that both depression and PTSD are highly prevalent in war survivors who stayed in the area of conflict. Yet, future research on this topic need to focus on psychometric properties of instruments used to assess psychopathology among war survivors. Notwithstanding this limitation, there is an urgent need for large-scale mental health programs that are appropriate for war-affected countries with limited resources and address depression as much as PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
78
4
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 64 publications
11
78
4
11
Order By: Relevance
“…Poverty, substance abuse, and violence against women are associated with fragile states and vulnerable settings [50]. A recent systematic review suggested that both depression and posttraumatic stress disorder were highly prevalent in war survivors who stayed in areas of con ict [51][52][53]. Even refugees who live abroad continue to suffer mental health problems due to the horri c sciences and scary journey to safe places [54].…”
Section: Discussionmentioning
confidence: 99%
“…Poverty, substance abuse, and violence against women are associated with fragile states and vulnerable settings [50]. A recent systematic review suggested that both depression and posttraumatic stress disorder were highly prevalent in war survivors who stayed in areas of con ict [51][52][53]. Even refugees who live abroad continue to suffer mental health problems due to the horri c sciences and scary journey to safe places [54].…”
Section: Discussionmentioning
confidence: 99%
“…Poverty, substance abuse, and violence against women are associated with fragile and vulnerable settings [33]. A recent systematic review suggested that both depression and post-traumatic stress disorder were highly prevalent in war survivors who stayed areas of conflict [34][35][36]. Even refugees who live abroad continue to suffer mental health problems due to the horrific sciences and scary journey to safe places [37].…”
Section: Discussionmentioning
confidence: 99%
“…A study of University students in the Gaza Strip revealed an association between war trauma and anxiety . Another study by Morina et al showed comorbidity for PTSD and depression among survivors in war‐afflicted regions. These findings add evidence to the perspective that PTSD and depression are the major disorders following traumatic events, predisposing to the development of comorbidities …”
Section: Introductionmentioning
confidence: 98%